A Complexidade da Administração/Gestão Escolar, Limites e Possibilidades - Militão, Andréia Nunes [UNESP] (2015)
This thesis was developed by the Program of Graduate Studies in Education of the Faculty of Science and Technology / Universidade Estadual Paulista and is linked to the research line Public Policy, School Organization and Teacher Education. It had as its object of analysis administration / management that takes place in schools. We take for granted that the School Administration / Management as field of knowledge was played by two opposing views: one that advocated that this was dependent on the General Theory of Administration; and another, who defended the specificity of School Administration. Throughout the twentieth century, these two concepts have polarized the debate on the School Administration / Management and hegemonized the field. The first seeks to put it as a mainly technical activity, prevalent in the 1960s and 1970s; the second emerges from the 1980s, seeking the specificity of Administration / School management, enhancing its political dimension. This treatment resulted, in the studies field and even in the formulation of educational policies, the sidelining of its pedagogical dimension. We seek to answer the question: What are the limits and possibilities of action of the administration / school management in the context of a state school in the state of São Paulo? Departig from this problem, we seek to answer the following guiding research questions: What are the characteristics that differentiate the school administration / management of business administration? What are the concepts underlying the concepts of school administration / management present in the formulations of SEE / SP? How do the technical, political and pedagogical dimensions interact within school administration / management?...